INTEGRATION OF LOCAL CULTURE IN ARABIC LESSON MATERIALS IN MADRASAH TSANAWIYAH DARUL HIKMAH SINJAI - Darda, Abu; Muzakkir, Muzakkir; Haniah, Haniah (Program Pascasarjana, UIN Alauddin Makassar, 2020)
This study aims to explore procedures or steps for the development of Arabic subject matter through the integration of local culture in Sinjai Regency into Arabic subject matter at Madrasah Tsanawiyah Darul Hikmah Sinjai and test the feasibility of Arabic language subject matter that is integrated with the local culture of Sinjai district. at Madrasah Tsanawiyah Darul Hikmah Sinjai. This research is a type of research and development or Research and Development (R&D) using four stages of research, namely, the data collection stage, the planning stage, the product development stage, and the product validation and testing stage. The instruments used were questionnaires, interviews and, observations. The results showed that the process of developing Arabic subject matter by integrating local Sinjai culture was carried out in six steps as follows, conducting field studies and literature studies on Sinjai local culture, determining and compiling materials, integrating local culture into Arabic subject matter for class VII Madrasah Tsanawiyah Arabic. into Arabic, material systematization, material validation includes internal validation and external validation. the internal test percentage reached 64.02%. And the external test results using the Wilcoxon type nonparametric statistical analysis is .003 which means less than 0.05 (003 <0.05), these two test results indicate that the product is suitable for use.